Efeitos agudos de diferentes intensidades do exercício aeróbio na resposta hipotensora pós-exercício em pessoas com Síndrome de Down - Bezerra, Maria Edilma da Silva (2018)
Studies have shown that even a single session of physical exercise lowers blood pressure after its completion. This phenomenon is called post-exercise hypotension (PEH), and has been considered as a non-pharmacological way to control blood pressure. However, there are no studies regarding the occurrence of PEH after acute exercise in individuals with Down Syndrome (DS). This study aimed to analyze the occurrence of PEH in these individuals and the possible role of exercise intensity. Ten individuals with DS, of both genders, participated in the study (age, 29 ± 7 years, body mass, 60.7 ± 9 kg, height, 1.48 ± 0.11 cm and BMI, 27.6 ± 2.4 kg/m²). Volunteers randomly underwent two sessions of exercise on a stationary bike for 20 minutes and a sham control session. Heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured after 15 minutes of resting, at the 20th minute of each exercise session or control, and at 15th, 30th and 45th minutes of post-exercise recovery. Both moderate and intense exercise performed acutely increased SBP (p<0.001; p<0.01, respectively) with no effect on DPB levels in individuals with DS. However, neither the moderate nor the intense exercise were enough to elicit PEH. The results indicated that individuals with DS may not present PEH for the intensities, duration and exercise mode as applied in the present investigation. While additional studies with different exercise strategies are needed, our findings contribute to the body of literature regarding the PEH responses in adults with DS.